Evaluation of Somatic Hypermutation Status in Chronic Lymphocytic Leukemia (CLL) in the Era of Next Generation Sequencing - Gupta, Sanjeev Kumar; Viswanatha, David S.; Patel, Keyur P. (Frontiers in Cell and Developmental Biology, 2020)
Somatic hypermutation (SHM) status provides an important prognostic indicator for chronic lymphocytic leukemia (CLL), a very common type of mature B-cell leukemia. Owing to the adverse prognosis associated with an unmutated immunoglobulin heavy chain variable (IGHV) status, SHM testing is performed as a standard of care in CLL. Conventionally, SHM testing has been performed using labor intensive and primarily analog Sanger sequencing method following PCR amplification of the clonal immunoglobulin gene rearrangements in CLL cells. In comparison, recent availability of next generation sequencing (NGS) allows more versatile detection and direct identification of clonal immunoglobulin sequences in neoplastic B-cell populations. The ability to identify specific clonal IGHV signature(s) in both baseline (diagnostic) and post-treatment settings enables unique clinical applications of NGS such as determination of SHM status, minimal residual disease monitoring, clonal heterogeneity and IGHV receptor stereotypy. We provide a review of current practices and recommendations for SHM determination using NGS including examples of difficult cases.